Health professionals knowledge of telemedicine and its associated factors working at private hospitals in resource-limited settings - Wubante, Sisay Maru; Tegegne, Masresha Derese (Frontiers in Digital Health, 2022)
Abstract Introduction: in resource-limited settings incorporating the Telemedicine system into the healthcare system enhances exchanging valid health information for practicing evidence-based medicine for the diagnosis, treatment, and prevention of diseases. Despite its great importance, the adoption of telemedicine in low-income country settings, like Ethiopia, was lagging and increasingly failed. Assessing the knowledge of health professionals before the actual adoption of telemedicine is considered the prominent solution to tackle the problem. Objective: This study aimed to assess health professionals' Knowledge and its associated factors in the Telemedicine system at private hospitals in Ethiopia in 2021. Method: An institution-based cross-sectional study was employed among 423 health professionals from March 3 to April 7 2021 at private hospitals in Amhara Region. A pretested self-administered questionnaire was used to collect the data. The data were analyzed by SPSS version 20 software. Descriptive statistics and bi-variable and multi-variable logistic regression analyses were performed. An adjusted odds ratio (AOR) with 95% CI was used to determine the s association between the independent and the outcome variable. Result: near two-third of health professionals have good knowledge on Telemedicine . Variables like computer literacy (AOR = 2.9; 95% CI: [1.8, 4.6]), computer training (AOR = 2.0; 95% CI: [1.2, 3.3]), Internet access at office (AOR=2.1; 95%CI: [1.3, 3.4]), Own personal computer(AOR = 1.7; 95% CI: [1.1, 2.9]) and were significantly associated with knowledge on Telemedicine . Conclusion and Recommendation: In general health professionals had good knowledge of the Telemedicine system. Inclusive packages of capacity by training among health professionals are fundamental for the successful implementation of telemedicine.